Metabolomic analysis of lung epithelial secretions in rats: An investigation of bronchoalveolar lavage fluid by GC-MS and FT-IR. (1st November 2014) - Qamar, Wajhul; Ahamad, Syed Rizwan; Ali, Raisuddin; Khan, Mohammad Rashid; Al-Ghadeer, Abdul Rahman
ABSTRACT Objective: Rat bronchoalveolar lavage fluid (BALF) metabolome can be used to obtain valuable, precise, and accurate information about underlying lung conditions in an experiment. The present study focuses on the evaluation of the lung epithelium metabolome in a rat model using techniques including bronchoalveolar lavage, gas chromatography-mass spectroscopy (GC-MS), and Fourier transform infrared spectroscopy (FT-IR). Materials and methods: Untargeted metabolites in BALF were extracted in ethyl acetate and derivatized by standard methods for the analysis by GC-MS. FT-IR spectra of ethyl acetate extract of BALF were obtained and read for the characteristic fingerprint of rats under investigation. Analyses were done in individual animals to obtain consistent data. BALF cells were counted by flow cytometry to monitor any inflammatory condition in rats. Results: FT-IR analysis finds two peaks which are characteristically different from the extract medium, which is ethyl acetate. FT-IR peaks correspond to that of amino acids and carbohydrates, including β-D-glucose, α-D-glucose, and β-D-galactose. GC-MS evaluation of the BALF finds several products of the metabolism or its participants. Main compounds in the BALF detected by GC-MS include succinate, fumarate, glycine, alanine, 2-methyl-3-oxovaleric acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octanoic acid, trans-9-octadecanoic acid, octadecanoic acid, and Prostaglandin F1α. Conclusion: Several research reports reveal metabolomic parameters in murine model lung tissue or BALF, but they rarely reported a complete metabolomics model profile, particularly in rats. The present data of GC-MS and FT-IR suggest that the set up can be exploited to study metabolomic alterations in several lung conditions including acute lung toxicity, inflammation, asthma, bronchitis, fibrosis, and emphysema.